Tracking key CAADP indicators and implementation processes [In the 2017-2018 ATOR] - Makombe, Tsitsi; Tefera, Wondwosen; Benin, Samuel (International Food Policy Research Institute, 2018)
In line with the role of the ATOR as the official monitoring and evaluation report for CAADP, Chapter 12 monitors progress on CAADP indicators outlined in the CAADP Results Framework 2015–2025. The chapter also reviews progress in the CAADP implementation process across the continent, including a look at trends in government social protection expenditures.